Role of chemokines in promoting instability of coronary atherosclerotic plaques and the underlying molecular mechanism - Zhong,Z.X. (2015)
Our aim was to investigate the role of chemokines in promoting instability of coronary atherosclerotic plaques and the underlying molecular mechanism. Coronary angiography and intravascular ultrasound (IVUS) were performed in 60 stable angina pectoris (SAP) patients and 60 unstable angina pectoris (UAP) patients. The chemotactic activity of monocytes in the 2 groups of patients was examined in Transwell chambers. High-sensitivity C-reactive protein (hs-CRP), monocyte chemoattractant protein-1 (MCP-1), regulated on activation in normal T-cell expressed and secreted (RANTES), and fractalkine in serum were examined with ELISA kits, and expression of MCP-1, RANTES, and fractalkine mRNA was examined with real-time PCR. In the SAP group, 92 plaques were detected with IVUS. In the UAP group, 96 plaques were detected with IVUS. The plaques in the UAP group were mainly lipid 51.04% (49/96) and the plaques in the SAP group were mainly fibrous 52.17% (48/92). Compared with the SAP group, the plaque burden and vascular remodeling index in the UAP group were significantly greater than in the SAP group (P<0.01). Chemotactic activity and the number of mobile monocytes in the UAP group were significantly greater than in the SAP group (P<0.01). Concentrations of hs-CRP, MCP-1, RANTES, and fractalkine in the serum of the UAP group were significantly higher than in the serum of the SAP group (P<0.05 or P<0.01), and expression of MCP-1, RANTES, and fractalkine mRNA was significantly higher than in the SAP group (P<0.05). MCP-1, RANTES, and fractalkine probably promote instability of coronary atherosclerotic plaque.